Dynamic Resource Block Allocation and Isolation in Network Slicing - Nidhi (2022)
Network slicing is crucial in 5G and its evolution concerning user-centric services. By allocating independent resources, like link bandwidth, computing/processing capabilities and spectrum, to address users’ requests, slicing serves the end-to-end verticals or services. gNodeB (gNB) allocates the bandwidth resources to transmit/receive data to User Equipments (UEs). Resources Blocks (RBs) are the smallest resource entities assigned to a single user. In 5G New Radio (NR), the timedomain resource allocation defines the allocated symbols (OFDM symbols), while the frequency-domain allocation illustrates the RBs (sub-carriers) allocation to the UE. RB comprehends 12 subcarriers in the frequency domain with a flexible RB bandwidth, unlike LTE-A. It is critical to provide enhanced services to different users. There have been several works on challenges to enable a multi-tenant and service RAN while providing isolation to the slices. This work proposes a detailed approach for creating slices based on the demanded services, resource virtualization and isolation. The focus is on resource sharing algorithms at the Slice Orchestrator (SO) level. These virtual network slices support a wide range of services and applications categorized into the Enhanced Mobile Broadband, Ultra-Reliable and Low-Latency Communications and Massive Machine-Type Communications megatrends. The paper also provides an overview of standardization activities and evolving requirements to support use cases and services like Holographic Telepresence, Automotives, among other.